Social capital and social enterprise performance in Pakistan social innovation as a proposed mediator - Abas, Javaria; Arshad, Darwina; Subramaniam, Chandrakantan (2019)
This conceptual paper is an attempt to understand the ways through which the social enterprises sustain and perform in resource poor environment of bottom of the pyramid (BOP) market Pakistan. An effort is made to understand the relationship between the key resource mobilization strategy i.e. social capital and social enterprise performance. Social capital can be explained as a key game plan of the social enterprises who gear up to address the gaps left by market and governments failures When surrounded by resources and institutional constraints without any political and regulatory support, the resources embedded in one’ s network plays a key role in achieving the double bottom line of the social ventures by introducing the novel solutions to the most pressing problem of the society. Lack of studies that treats social innovation as a mediator has led us to propose it as an important variable that can lead us to the achievement of the dual goals of profit making along with social impact of social enterprises. Therefore, social innovation plays the important role of a link in this proposed integrated model. The resource-based theory (RBT) is used as the under-pinning theory for this study. This study can give valuable insights to for profit and not for profit companies both, who are aiming to generate social impact by generating enough revenues as well, about the possible scaling up strategy.